Cet emploi du temps : de l’entropie, du provisoire - Duhamel, Patrice (Ciel variable)

(untitled) (Les Productions Ciel variable, 2006)
Abstract The situations in which Erwin Wurm involves us can be fully inscribed under the sign of potentiality. Beyond metaphysics, Wurm is interested in making the actual physique of bodies speak. The physique conveys sloth, idiocy, and depression as forms of resistance, blockage, withholding, and play. Wurm's works, in presenting rather than, perhaps, representing the human figure, seem to suggest the possibility of short circuiting the image of the world that comes to us through convention as well as the behaviours that we are supposed to adopt.